Interplay between Accounting and Prudential Regulation - Bertomeu, Jeremy; Mahieux, Lucas; Sapra, Haresh (The Accounting Review, 2023)
ABSTRACT We develop a model in which accounting information and prudential regulation interact to affect banks’ incentives to originate loans. Prudential regulators impose capital requirements to prevent banks from taking excessive risk. However, regulators cannot commit to ex ante efficient intervention and, instead, respond to ex post accounting information. We show that capital requirements and accounting measurement are substitutes when considered separately. By contrast, when considered jointly, accounting measurement and capital requirements are complementary tools that affect the level and efficiency of credit decisions. Comparative statics link capital requirements, quality of accounting information, and regulatory intervention to credit market conditions. An upshot of our analysis is that by appropriately optimizing the information from expected loss models, prudential regulators may design looser capital requirements to spur more bank lending. JEL Classifications: G21; G28; M41; M48.